PENGARUH SISTEM PENGENDALIAN INTERN TERHADAP KINERJA ORGANISASI PERANGKAT DAERAH DENGAN SISTEM PENGUKURAN KINERJA SEBAGAI VARIABEL MEDIASI (Studi Empiris pada Organisasi Perangkat Daerah Kota Bukittinggi) - Nadhira, Hafifah Hasya; Rohman, Abdul (Diponegoro Journal of Accounting, 2021)
This aim of thif research is to examine the effect of internal control system on the organizational performance of regional apparatus with performance measurement system as a mediating variable in OPD Bukittinggi City. The dependent variable in this research is the organizational performance of regional apparatus. While the independent variable is internal control system also performance measurement system as a mediating variable.The sampling method used is purposive sampling. The sample in this research amounted to 115 respondents who are civil servants (PNS) in Bukittinggi City. The type of data used in this research is primary data by distributing questionnaires to respondents. Data analysis techniques used are simple linear regression analysis and path analysys processed using SPSS.The results showed that: (1) the intenal control system directly affects has a positive and significant effect on the performance of regional apparatus organizations in OPD Bukittinggi City,(2) the performance measurement system has a positive but insignificant effect on the performance of regional apparatus organizations in OPD Bukittinggi City, and (3) the internal control system indirectly has a positif but insignificant effect on the performance of regional apparatus organizations through the performance measurement system in OPD Bukittinggi City. This indicates that the performance measurement system is unable to mediate in the relationship between the internal control system and the performance of regional apparatus organizations.